KONDISI LINGKUNGAN FISIK HABITAT ANGGREK TERESTRIAL DI KAWASAN TAMAN NASIONAL LORE LINDU DESA MATAUE KECAMATAN KULAWI KABUPATEN SIGI - Tagentju, Rachel Jesika; Toknok, Bau; Korja, I Nengah (Universitas Tadulako, 2020)
Environmental conditions affecting the growth of terrestrial orchids and other orchids, namely altitude, temperature, sunlight and soil (place to grow). These factors are indispensable in the cultivation of orchid plants. Nowadays many people who love orchids or related institutions want to nurture and cultivate and preserve the plant but there is still much needed information about the environmental condition of the orchid habitat terrestrial. This research aims to know the physical environment of terrestrial orchid habitat in Mataue Village of Kulawi Sub-district of Sigi, implemented in late May until July 2018 with the survey method. Research using survey methods. Data retrieval is performed purposive sampling by retrieving data and samples in the field where terrestrial orchids are found. The data collected includes temperature, humidity, light intensity, altitude and soil pH. The results showed that of two types of terrestrial orchids observed each of the three individuals namely the Orchids Spathoglottis vanvuurenii J.J.Sm and Orchids Calanthe triplicate (Willemet) Ames at an altitude of 724 – 991 mdpl. Daily average light intensity ranges between 44%-49.7%, daily average air temperature ranges between 24,95 ° C-24.5 °c, average daily humidity ranges between 78.4%-79.5%, and soil pH in both types of terrestrial orchids ranged between 6.0 – 6.3.